2018
DOI: 10.1016/j.hrthm.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognized venous injuries after cardiac implantable electronic device transvenous lead extraction

Abstract: Microscopic venous injuries during lead extraction are common but often not recognized clinically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…This should, however, be interpreted with caution as microscopic evaluation of extracted leads by Tarakji and colleagues showed that over 15% of the patients showed signs of (often transmural) focal venous injury. Interestingly, only five major clinical complications (1.1%) occurred in that study population 19 . More research is needed to evaluate the effects of TLE induced endothelial damage.…”
Section: Discussionmentioning
confidence: 80%
“…This should, however, be interpreted with caution as microscopic evaluation of extracted leads by Tarakji and colleagues showed that over 15% of the patients showed signs of (often transmural) focal venous injury. Interestingly, only five major clinical complications (1.1%) occurred in that study population 19 . More research is needed to evaluate the effects of TLE induced endothelial damage.…”
Section: Discussionmentioning
confidence: 80%
“…In all patients transvenous lead placement results in encasement of the lead by fibrous tissue. In a Cleveland Clinic study, 6 861 extracted device leads of more than 1 year were examined histologically revealing dense fibrous tissue with the presence of calcification. In locations where the lead irritates the endothelium the inflammatory cascade results in proliferation of connective tissue attaching the lead to the vein (fibrous binding sites).…”
Section: Discussionmentioning
confidence: 99%
“…Adhesion caused by thrombo-fibrotic lead encapsulations (TFLE) is a serious secondary complication in cardiac arrhythmia treatment based on implantable electronic devices with transvenous leads (TVL) (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Despite ongoing progress in enhancing lead design reducing technical defects such as fractures and insulation defects, TLE is necessary for an infinitive period, particularly due to leadrelated infections. As a consequence, excessive TFLE persist as a serious challenge interfering with TLE, causing higher costs (51) and periprocedural risks (39), e.g., for vein injury (38). However, we actually assent to the view that moderate TFLE adhesions are desirable for leads due to a certain mechanical stability after implantation (24).…”
Section: Future Perspectivesmentioning
confidence: 99%